IGF-1 receptor regulates dynamic changes in neuronal polarity during cerebral cortical migration - Alvaro F. Nieto Guil (Nature Portfolio, 2017)
Abstract During cortical development, neurons undergo polarization, oriented migration and layer-type differentiation. The biological and biochemical mechanisms underlying these processes are not completely understood. In neurons in culture we showed that IGF-1 receptor activation is important for growth cone assembly and axonal formation. However, the possible roles of the insulin like growth factor-1 receptor (IGF-1R) on neuronal differentiation and polarization in vivo in mammals have not yet been studied. Using in utero electroporation, we show here that the IGF-1R is essential for neocortical development. Neurons electroporated with a shRNA targeting IGF-1 receptor failed to migrate to the upper cortical layers and accumulated at the ventricular/subventricular zones. Co-electroporation with a constitutively active form of PI3K rescued migration. The change of the morphology from multipolar to bipolar cells was also attenuated. Cells lacking the IGF-1 receptor remain arrested as multipolar forming a highly disorganized tissue. The typical orientation of the migrating neurons with the Golgi complex oriented toward the cortical upper layers was also affected by electroporation with shRNA targeting IGF-1 receptor. Finally, cells electroporated with the shRNA targeting IGF-1 receptor were unable to form an axon and, therefore, neuron polarity was absent.